Broadband 10 Gb/s operation of graphene electro‐absorption modulator on silicon. Issue 2 (11th January 2016) - Hu, Yingtao; Pantouvaki, Marianna; Van Campenhout, Joris; Brems, Steven; Asselberghs, Inge; Huyghebaert, Cedric; Absil, Philippe; Van Thourhout, Dries
Abstract : Graphene is considered to be a promising material for realizing ultra‐high bandwidth and broadband operation electro‐absorption modulators. However, demonstration of a graphene based modulator combining both properties in a single device is still lacking. In this work, the true potential of silicon integrated single layer graphene modulators is theoretically investigated and a broadband modulator operating at 10 Gb/s is demonstrated. Abstract: High performance integrated optical modulators are highly desired for future optical interconnects. The ultra‐high bandwidth and broadband operation potentially offered by graphene based electro‐absorption modulators has attracted a lot of attention in the photonics community recently. In this work, we theoretically evaluate the true potential of such modulators and illustrate this with experimental results for a silicon integrated graphene optical electro‐absorption modulator capable of broadband 10 Gb/s modulation speed. The measured results agree very well with theoretical predictions. A low insertion loss of 3.8 dB at 1580 nm and a low drive voltage of 2.5 V combined with broadband and athermal operation were obtained for a 50 μm‐length hybrid graphene‐Si device. The peak modulation efficiency of the device is 1.5 dB/V. This robust device is challenging best‐in‐class Si (Ge) modulators for future chip‐level optical interconnects.